The Evolution of Poverty during the Crisis in Indonesia, 1996–99 - Suryahadi, Asep; Sumarto, Sudarno; Suharso, Yusuf; Pritchett, Lant (World Bank, Washington, DC, 2015)
Poverty is intrinsically a complex social construct, and even when it is narrowly defined by a deficit of consumption spending, many thorny issues arise in setting an appropriate "poverty line". The authors limit themselves to examining how poverty - defined on a consistent, welfare-comparable basis - changed in Indonesia during a series of crises that began in august 1997. Using various data sets and studies, they develop a consistent series on poverty's evolution from February 1996 to August 1999. Specifically, they study the appropriate method for comparing changes in poverty between the February 1996 and February 1999 Susenas surveys. To set a poverty line for 1999 that is conceptually comparable to that for 1996 involves a standard issue of price deflation: How much would it cost in 1999 to purchase a bundle of goods that would produce the same level of material welfare as the money spent at the poverty line in 1996? Empirically, given major changes in the relative prices of food, the key issue is the weight given food prices in the price index. Using different deflators produces a range of plausible estimates, but they produce a range of plausible estimates, but they produce two "base cases": one working forward from 1996, and one working backward from 1999. If one accepts the official figure of 11.34 percent for February 1996, poverty increased from the immediate pre-crisis rate of about 7-8 percent in the second half of 1997, to the post-crisis rate of about 18-20 percent by September 1998, and 18.9 percent in February 1999. If one begins from the best estimate of the poverty rate in February 1999 (27.1 percent), poverty rose by 9.6 percentage points from 17.5 percent in February 1996. Since February 1999, poverty appears to have subsided considerably but - two years after the crisis started - is still substantially higher than it was immediately before the crisis.